Correlation between haemoglobin, leukocytes, HbA1c, and albumin levels with diabetic foot ulcer severity: a cross-sectional study - Heri Nugroho; Agung Putra; Ignatius Riwanto; Nur Anna Chalimah Sadyah (Faculty of Medicine, Universitas Islam Sultan Agung (UNISSULA), Indonesia, 2025)
Diabetic foot ulcers (DFUs) represent a serious complication of diabetes mellitus, associated with significant morbidity and healthcare costs. The progression of DFUs is influenced by systemic and local factors, including haemoglobin levels, leukocyte count, glycated haemoglobin (HbA1c), and serum albumin. This study aims to explore the relationship between these clinical parameters and the severity of DFUs. We enrolled 62 patients with DFUs and classified ulcer severity as mild, moderate, or severe according to the Wagner classification system. Using Spearman’s rank correlation, we found significant associations: lower hemoglobin and albumin levels correlated with more severe ulcers (ρ = -0.34, p= 0.0065; ρ = -0.41, p = 0.00084, respectively), while higher HbA1c and leukocyte counts were associated with increased ulcer severity (ρ = 0.62, p = 0.000; ρ = 0.40, p = 0.0013, respectively). These findings suggest that hematologic and biochemical markers may serve as valuable indicators of DFU progression, potentially guiding clinical decision-making and improving patient outcomes. Further research is needed to elucidate the underlying mechanisms and evaluate targeted interventions for this high-risk population.